How are firms affected by exchange rate shocks? Evidence from survey based impulse responses - Matthias Bannert; Dirk Drechsel; Heiner Mikosch; Samad Sarferaz (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper studies the effects of a change in the Swiss franc/euro exchange rate floor, as introduced by the Swiss National Bank in September 2011 using a survey based impulse responses analysis. Survey based impulse responses incorporate experimental settings into representative firm surveys, expose firm executives to treatment or shock scenarios and evaluate the effects of the shocks on executives' expected firm-level outcomes. Our results suggest that a change in the exchange rate floor from 1.20 to 1.10 Swiss francs per euro and a subsequent appreciation of the Swiss franc by the same magnitude considerably decreases expected turnovers, costs and profits of Swiss firms. Manufacturing turnover decreases by 3.3% within six months and by 4.3% within 18 months. Total costs decline by 1.3% within six months and 2.0% within 18 months, while profits shrink by 3.3% within six months. The effects are substantially lower for the service and the construction sector, but exhibit large variation across sub-sector industries. Panel regression analysis reveals that firm-specific export shares and intermediate goods import shares are key determinants of firms' turnover, costs and profits reactions.
Keywords: C83; C99; E37; F31; 330; Swiss franc/euro exchange rate floor; survey based impulse responses; macroeconomic shock identification; structural micro data; disaggregation